Action Ideas in Educating for Human Rights and Towards a Culture of Peace in Puerto Rico (In Factis Pax: Journal of Peace Education and Social Justice, 2009)
For this paper we engaged in the task of thinking about the field of education for human rights and peace in Puerto Rico. The existing ties between human rights education, peace education, and a culture of peace were our starting point. Five action-ideas  constitute the pillars for research and reflection in this paper: (1) equity and diversity, (2) quality of life, (3) intergenerational equity, (4) self-determination, (5) culture of peace and human rights.